Solid-phase synthesis of biaryl bicyclic peptides containing a 3-aryltyrosine or a 4-arylphenylalanine moiety - Ng-Choi, Iteng; Oliveras, Àngel; Feliu, Lidia; Planas, Marta (Beilstein Journal of Organic Chemistry, 2019)
A methodology for the solid-phase synthesis of biaryl bicyclic peptides containing a Phe-Phe, a Phe-Tyr or a Tyr-Tyr motif has been devised. This approach comprises two key steps. The first one involves the cyclization of a linear peptidyl resin containing the corresponding halo- and boronoamino acids via a microwave-assisted Suzuki–Miyaura cross coupling. This step is followed by the macrolactamization of the resulting biaryl monocyclic peptidyl resin leading to the formation of the expected biaryl bicyclic peptide. This study provides the first solid-phase synthesis of this type of bicyclic compounds being amenable to prepare a diversity of synthetic or natural biaryl bicyclic peptides.
Keywords: borylation; cross-coupling; cyclization; macrocycles; solid-phase synthesis